Structural and functional significance of microsatellites - Sjakste, T.; Paramonova, N.; Sjakste, N. (Вiopolymers and Cell, 2016)
Here we review literature data on impact of microsatellite repeats on DNA and chromatin structure and the results of studies on association between the length of microsatellite repeats and predisposition to pathologies. The DNA secondary structure is modified in microsatellite sites, the repeats favor formation of Z-DNA, hairpins, triplexes and quadruplexes. The chromatin structure and chromatin loop organization are also modified in microsatellite sites. The data of association studies are classified according to the localization of the microsatellite: in the gene promoter, in exon 1 part coding the signal sequence, in the gene introns, coding areas and 3’-UTRs.